2006
DOI: 10.1080/02770900500447052
|View full text |Cite
|
Sign up to set email alerts
|

Asthma Patients' Assessments of Health Care and Medical Decision Making: The Role of Health Literacy

Abstract: The objectives of this cross-sectional study were to measure health literacy and its associations with asthma patients' assessments of care and their desire to participate in making decisions about their treatment. A total of 175 patients completed the Test of Functional Health Literacy in Adults and questions about satisfaction with asthma status, access to care, quality of care, and the desire to participate in treatment decisions. Patients' mean age was 42 years and 83% were women. Lower literacy was associ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
55
2

Year Published

2007
2007
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 77 publications
(62 citation statements)
references
References 21 publications
5
55
2
Order By: Relevance
“…Further, we found that overall knowledge of asthma triggers and management was high among caregivers of high healthcare utilizers and did not differ by ethnicity. Our findings differ from prior ASTHMA KNOWLEDGE, APTITUDE, AND PRACTICEstudies that report limited parental asthma knowledge, 18,19 primarily related to parental literacy, 20 among caregivers of children with asthma in both Hispanic and AA households. 7 However, despite having high knowledge levels, the caregivers had high usage of ED and hospitalization for management of their child's asthma.…”
Section: Discussioncontrasting
confidence: 56%
“…Further, we found that overall knowledge of asthma triggers and management was high among caregivers of high healthcare utilizers and did not differ by ethnicity. Our findings differ from prior ASTHMA KNOWLEDGE, APTITUDE, AND PRACTICEstudies that report limited parental asthma knowledge, 18,19 primarily related to parental literacy, 20 among caregivers of children with asthma in both Hispanic and AA households. 7 However, despite having high knowledge levels, the caregivers had high usage of ED and hospitalization for management of their child's asthma.…”
Section: Discussioncontrasting
confidence: 56%
“…Paradoxically, an appropriate asthma action plan relies upon the parent providing accurate information to the healthcare provider. Low literacy adults with asthma often lack these skills; [14][15][16] low literacy parents likely lack them as well. While health literacy may be difficult to change, how and what skills parents are taught has the potential to improve children's asthma outcomes.…”
Section: Discussionmentioning
confidence: 99%
“…Studies among adults with asthma indicate that lower health literacy predicts worse asthma outcomes, 14 medical decision making, knowledge, and selfmanagement skills, such as correctly using a meter-dose inhaler and communicating with their healthcare provider. 15,16 Parents need these same skills, as well as reading and numeracy skills, to manage their children's asthma successfully in order to achieve better asthma health outcomes.…”
Section: Introductionmentioning
confidence: 99%
“…A total of 13 articles were thus identified, and the main findings of these articles are summarized in Table I. [18][19][20][21][22][23][24][25][26][27][28][29][30] The studies included in these articles differ with regard to the instrument used to assess HL, the thresholds used to define categories of HL, and the variables included in multivariate analyses.…”
Section: Hl and Asthmamentioning
confidence: 99%